2020
DOI: 10.24215/23143738e081
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de Ecuaciones Estructurales (Con estimación PLS) basado en calidad de servicio y lealtad del Cliente de las Cajas Rurales Peruanas

Abstract: El principal objetivo de la investigación fue analizar la calidad del servicio de las cajas rurales de ahorro y crédito e investigar su influencia en la lealtad de los clientes en el sector microfinanciero peruano. Se utilizó la técnica de la encuesta donde se recopilaron datos de 385 clientes a través del cuestionario mediante el muestreo aleatorio simple. La metodología se realizó mediante Modelos de Ecuaciones Estructurales (SEM) y para evaluar el modelo teórico se optó por la técnica de análisis de Mínimos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Furthermore, to test the proposed theoretical model, it was necessary to apply the methodology of structural equations to respond to the hypotheses raised in the research. A similar application of this methodology of structural equations was developed in the research (Norabuena et al 2021)…”
Section: Statistical Data Analysis Techniquesmentioning
confidence: 99%
“…Furthermore, to test the proposed theoretical model, it was necessary to apply the methodology of structural equations to respond to the hypotheses raised in the research. A similar application of this methodology of structural equations was developed in the research (Norabuena et al 2021)…”
Section: Statistical Data Analysis Techniquesmentioning
confidence: 99%
“…In Peru, Norabuena et al (2021) showed that there is a significant effect between service quality and customer loyalty in rural savings and credit banks, concluding that managers and tellers should better implement their quality policies. On the other hand, Quintero et al (2019) stated that there is a dependence between service quality and loyalty, which allowed them to conclude that loyalty in the service sector is a consequence of good service quality since a customer will always choose to buy a certain quality product when that company offers it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Este valor debe ser mayor que los valores de cada fila y columna respectivamente. Para analizar la validez discriminante se obtuvieron las cargas factoriales y cargas factoriales cruzadas (Norabuena-Mendoza et al, 2020). Siendo así, las cargas factoriales deben ser superiores a las cargas factoriales cruzadas (Ruiz et al 2010)…”
Section: Cargas Factoriales Cruzadasunclassified